Features and Formation Mechanism of the Jiaopenba Landslide, Southwestern Sichuan Province, China - Shen, Tong; Wang, Yunsheng; Zhao, Xun; Liu, Heng; Wu, Xuyang; Chu, Yapei; Zhai, Panpan; Han, Yang (Frontiers in Earth Science, 2022)
The Jiaopenba landslide, which represents a typical large basalt high-speed remote landslide, is located in Emeishan City, southwestern Sichuan Province, China. Based on the field investigation, the characteristics of Jiaopenba landslide has been revealed: The Jiaopenba landslide occurred on the steep Mount Emei. Landslide materials with a volume of approximately 6.75×108m3 slid down from a high position, forming a large-scale high-speed remote debris flow, with the farthest sliding distance of about 7.5km. The landslide area is located in the west wing of Emeishan anticline, which is cut by faults to form a monoclinal fault block mountain. Although the shear outlet of the landslide is near the slope toe and does not have good free conditions, there are faults passing through the slope toe of the bedding slope of the fault hanging wall, the landslide is affected by the fault activity, the integrity of the layered slope is poor. When the foot of the slope is empty, the fault zone is compressed and plastic extrusion, which leads to bedding slip of the slope rock mass and greatly weakens the interlayer bonding force. When coupled with long structural planes on both sides to form side crack planes, a large-scale inclined plate structure is formed. Under the action of strong earthquake and other external forces, the rock mass near the fault can be damaged by tension, and a large-scale high-position landslide can be formed by the mode of compression-slip-tension fracture.